Impact of School-Based Health Education Intervention on the Incidence of Soil-transmitted Helminths in Pupils of Rural Schools, Kogi East, North Central Nigeria. - Yaro, Clement Ameh; Kogi, Ezekiel; Luka, Sodangi Abdulkarim (Preprints, 2020)
Background: The negative impact of soil-transmitted helminths (STHs) in Nigeria is enormous posing serious public health issues. This study was undertaken to investigate the impact of health education intervention on re-infection of STHs in pupils of rural schools of Kogi East, North Central Nigeria. Methods: A cross-sectional survey was carried out in 45 schools to determine the prevalence of STHs in the 9 local government areas of Kogi East. Stool samples were collected and examined for STHs. A total of 10 schools with the highest prevalence were selected for the follow-up study, 5 schools were dewormed and given health education (DHE) intervention while the other 5 schools were dewormed only (DO). Reassessment of schools for re-infection was carried out for a period of 12 months. Data obtained were analyzed using descriptive statistics. Student t-test was used to make comparison between interventions in the incidence of infections. Analysis was carried out at p<0.05.Results: Re-infection with STHs was observed from the 7th month of both interventions. In the 36th week (9th month), incidence observed in schools given DHE schools (4.79%, 8 pupils) were higher than in DO schools (3.19%, 5 pupils), no significant difference (t = -0.840, p = 0.426) between the interventions. Also, at the 48th week (12 th month), no significant difference (t = -0.346, p = 0.738) between the DHE schools (7.19%, 12 pupils) and DO schools (6.37%, 10 pupils). Hookworms had the highest incidence in DHE (6.6%, 11 pupils) and DO (6.4%, 10 pupils) schools among the STHs. A. lumbricoides incidence was low and was observed in a school given DHE (0.6%, 1 pupil). S. stercoralis was not observed throughout. At 48th (12 th month), an incidence of 6.37% was observed compared to 32.03% prevalence at baseline in the DO schools and an incidence of 7.11% and prevalence of 36.09% in the DHE schools. Significant difference(p<0.05) exist between baseline and intervention. Conclusion: Non-dewormed individuals at the community levels may have contributed to the poor performance of health education. Community-based deworming should be encouraged alongside improvement in the water, sanitation and hygiene infrastructures at both school and home.
Keywords: health education; deworming; soil-transmitted helminths; Kogi East; Nigeria; Ahmadu Bello University; ACENTDFB